2022
DOI: 10.1002/jia2.25884
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of female sex workers living with HIV in South Africa: a cross‐sectional study

Linwei Wang,
David W. Dowdy,
Carly A. Comins
et al.

Abstract: Introduction:Health-related quality of life (HRQoL) is an important HIV outcome beyond viral suppression. However, there are limited data characterizing HRQoL of key populations, including female sex workers (FSW) living with HIV. Methods: We used baseline data (22 June 2018-23 March 2020) of FSW who were diagnosed with HIV and enrolled into a randomized trial in Durban, South Africa. HRQoL information was collected by a generic preference-accompanied tool with five domains (EQ-5D), and summarized into a singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Interventions supporting stable housing may have multifaceted impacts for HIV treatment access, storage, and daily adherence, ultimately leading to optimal health outcomes and viral suppression. Finally, a complementary analysis among FSW at enrollment into Siyaphambili also reinforced the importance of structural determinants, finding that drug use, violence, stigma, and lack of ART use all contributed to lower health-related quality of life scores [ 71 ]. Taken together these multilevel determinants iteratively shape HIV transmission dynamics and heterogeneously impact FSW living with HIV, disproportionally affecting women at increased vulnerability [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions supporting stable housing may have multifaceted impacts for HIV treatment access, storage, and daily adherence, ultimately leading to optimal health outcomes and viral suppression. Finally, a complementary analysis among FSW at enrollment into Siyaphambili also reinforced the importance of structural determinants, finding that drug use, violence, stigma, and lack of ART use all contributed to lower health-related quality of life scores [ 71 ]. Taken together these multilevel determinants iteratively shape HIV transmission dynamics and heterogeneously impact FSW living with HIV, disproportionally affecting women at increased vulnerability [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model using overall QoL showed that enacted sex work stigma, internalized sex work stigma and enacted HIV stigma were associated with a decrease in prevalence of high overall QoL. Another analysis using the same study population similarly linked internalized stigma with overall QoL using the EuroQoL five dimension, three-level questionnaire (EQ-5D-3L) [ 63 ]. This previous analysis also reported that increased internalized and experienced stigma were associated with a lower EuroQoL visual analogue scale (EQ-VAS).…”
Section: Discussionmentioning
confidence: 99%
“…Siyaphambili study procedures, including recruitment and sampling methods, are reported in detail elsewhere. [19][20][21] Briefly, peers conducted study recruitment activities from a mobile van in mapped priority sex work venues in eThekwini Municipality (Durban) and from a drop-in center managed by TB HIV Care, the largest key populationsfocused HIV service provider within the district. Across community and clinical settings, peers approached potentially eligible women and invited them to screen for study enrollment.…”
Section: Design and Populationmentioning
confidence: 99%